Running out : in search of water on the High Plains - Bessire, Lucas (Princeton University Press, 2021)
"This book-the first ethnography of water conservation on the Great Plains-provides an account of High Plains aquifer decline through an exploration of the different ways in which heartland residents inhabit and understand the imminent depletion of groundwater. This literary ethnography offers a vividly sketched look into the lives and stories of this community, based on interviews with members of the community such as fellow farmers and state regulators, woven together with historical data, journalistic documentation, and Bessire's personal reflections of his family's lived experiences. (Five generations of the author's family have lived in the region as farmers and ranchers.)"--